Community-Based Conservation and Management of Chelonians in the Amazon - Andrade, Paulo Cesar Machado; de Oliveira, Paulo Henrique Guimarães; de Lima, Aldeniza Cardoso; da Mota Duarte, João Alfredo; da Silva Azevedo, Sandra Helena; de Oliveira, Anndson Brelaz; de Almeida, Carlos Dias; da Silva, Eleyson Barboza; Garcez, Jânderson Rocha; da Silva Pinto, José Ribamar; da Silva, Liriann Chrisley Nascimento; Monteiro, Midian Salgado; et al. (Frontiers in Ecology and Evolution, 2022)
Chelonians represent an important resource in the Amazon, either as a source of protein at the base of the food chain of aquatic and transition ecosystems, or in the dispersion of seeds of plants from floodplains and flooded forests. The consumption and predatory exploitation of their meat and eggs by local populations has been, and still is, one of the main threats to these animals. Community-based conservation projects allied to official protection programs have been restoring populations of chelonians of the genus Podocnemis throughout the Amazon since 1974. In this study, we analyzed the historical series of protection data of Podocnemis expansa, P. unifilis, P. sextuberculata and P. erythrocephala in areas protected by the government and communities in the Amazonas state and northwest of Pará state. Between 1974 and 2019, 230,444 nests and 21,350,201 hatchlings of P. expansa, 170,076 nests and 3,229,821 hatchlings of P. unifilis, 647,715 nests and 6,410,092 hatchlings of P. sextuberculata and 24,617 nests and 168,856 hatchlings of P. erythrocephala were protected. Community protection schemes emerged in 1990, and covered 80.7% of the areas and produced 64.2% of P. unifilis hatchlings and 44.6% of P. sextuberculata hatchlings. The areas with the highest production of P. expansa remain under government protection (57.4%). Using the time series of production of nests and hatchlings per beach, logistic growth curves were estimated, and the values of r and K were compared between two protection systems (government and community). Beaches controlled by the government showed higher support capacity in the production of nests (1,910.7±1,035) and hatchlings (211,513±93,031) of P. expansa and P. sextuberculata (81,160±34,924 hatchlings). However, the communities were more efficient in protecting nests (r=0.102±0.2315) and hatchlings (r=0.282±0.166) of P. unifilis. Community-based protection and monitoring programs are an important component that should be incorporated by the government's environmental agencies for the management and conservation of turtles in the Amazon.